Bestiality in the West: Geraldus of Wales’s Fantasies about the Irish Borderlands: A Medieval Colonialist’s Worldview - Classen, Albrecht (Global Journal of Cultural Studies, 2024)
Medieval legal, theological, and scientific discourse was highly interested in the monstrous element both out of simple curiosity and because it represented ‘the other’ in epistemological terms. Monsters, however, were normally far-removed, and did not create real fear because they were the products of human fantasy. Bestiality, on the other hand, constituted a direct threat to the well-being of human society, breaching the boundary between humans and animals in a dangerous fashion. This article examines the discourse on bestiality in Geraldus of Wales’s Topographia Hibernica (1187) through which he succeeded to erect a cultural barrier between the Irish on the one hand and the British on the other and to project them as uncivilized, backwards, and as a people that would need to be colonized. Geraldus thus emerges as a stalwart ‘imperialist’ avant la letter. A critical reading of his treatise allows us to apply this ‘anachronistic’ term to this influential medieval writer, which in turn makes it possible to extent our modern anti-colonialist discourse to the high Middle Ages, and perhaps also vice-versa.